Quantitative analysis of traditional knowledge of medicinal plants in San Rafael, Coxcatlan, Tehuacán-Cuicatlán Valley, Puebla, Mexico - Canales Martínez, Margarita; Hernández Delgado, Tzasná; Caballero Nieto, Javier; Romo de Vivar Romo, Alfonso; Durán Díaz, Ángel; Lira Saade, Rafael (Instituto de Ecología, A.C., 2006)
This study was directed to document the consistency and distribution of traditional knowledge concerning the medicinal flora at the village of San Rafael, municipality of Coxcatlán. Two types of interviews (free listing and structured) were applied to 60 informants. Data analysis using chi-square and the Spearman coefficient, revealed no significant differences in knowledge on medicinal plants between gender, age, occupation, provenance and residence time in the village. Nevertheless, it was observed that older people recognized a larger number of plants than the younger ones. Correspondence analysis revealed a non-clear pattern in the distribution of the knowledge of medicinal flora. The analysis of the results obtained from structured interviews and adjusted to a linear model versus the results of the first interviews showed the strength and congruence of the traditional knowledge by the inhabitants of San Rafael about medicinal plants. The interviewed informants recognized more than 90% of the species they mentioned in the open interviews and also mentioned the same medicinal use. The size of the village and the systematic interactions between its inhabitants, might explain the homogeneity of the traditional knowledge of San Rafael’s residents concerning the healing properties of the plants.